2017
DOI: 10.1007/s00421-017-3787-6
|View full text |Cite|
|
Sign up to set email alerts
|

A mathematical model of the effects of resistance exercise-induced muscle hypertrophy on body composition

Abstract: The model is able to reproduce the time course of change in LM in response to RE and can be used to generate a simulated cohort for in silico clinical studies. Simulations suggest that the additional LM generated by RE may shift the body composition to a healthier state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Nevertheless, the work by Morton et al [6] focuses on the effect of protein intake on muscle gain, without addressing the effect of training without protein supplementation; while the model created by Torres et al is a theoretical model focused on fat loss and lean mass gain in obese people, not determining the effect of the different training parameters. In fact, the authors declare that further models may be developed and redefined to include parameters they had not addressed [7]. Therefore, it seems that a really integrative model, taking into account all the variables that influence muscle hypertrophy, is currently lacking.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the work by Morton et al [6] focuses on the effect of protein intake on muscle gain, without addressing the effect of training without protein supplementation; while the model created by Torres et al is a theoretical model focused on fat loss and lean mass gain in obese people, not determining the effect of the different training parameters. In fact, the authors declare that further models may be developed and redefined to include parameters they had not addressed [7]. Therefore, it seems that a really integrative model, taking into account all the variables that influence muscle hypertrophy, is currently lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, muscle hypertrophy in humans is influenced by numerous variables, from those inherent to exercise such as mechanical tension, metabolic stress, muscle damage, training volume and intensity [8,9]; to those being specific to the individual (age, sex, previous training status, etc.) [10], or those related to energy balance and protein metabolism [6,7]. Consequently, any study aiming to analyse and estimate muscle hypertrophy in humans must precisely address all confounding factors that may completely alter the final results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that older individuals with sarcopenia who receive RET interventions with training durations of 8–24 weeks can achieve greater changes in appendicular LM (MD = 0.45–1.20 kg) [ 15 , 48 , 49 , 50 ] and AMI (MD = 0.17–1.16 kg/m 2 ) [ 48 , 49 , 50 ] compared with their untrained peers, regardless of the RET protocol. The training period required to achieve evident LM gains in response to RET was estimated as 8–12 weeks for older individuals [ 51 ]. Following previous results, a 12-week RET program was employed in the present study for overweight and obese older women who had received TKR; the EG made greater gains in appendicular LM (MD = 1.09 kg) and AMI (MD = 0.24 kg/m 2 ) than did the CG.…”
Section: Discussionmentioning
confidence: 99%
“…Torres et al [44] extended an energy balance model to account for the hypertrophic effects of resistance training and used the model for simulation studies. Moreover, the model was fit to data from elderly subjects following a resistance training routine.…”
Section: Existing Modelsmentioning
confidence: 99%